Analysis of Linear Consecutive-2-out-of-n: F Repairable System with Different Failure Rate - Özbey, Fahrettin; Gökdere, Gökhan (My University, 2021)
In the reliability analysis, when the reliability of a repairable consecutive-k-out-of-n system is considered, thecomponents are generally supposed to have an equal failure rate. In practice, this assumption may fail. Therefore,in this paper it is adopted that the lifetime of each component are random variables, exponentially distributed, withdifferent failure rates. The time required to repair is an exponential random variable and each component afterrepair is as durable as new. In this paper, we proposed a model for the state transition probability of this repairablesystem when components have unequal failure rates. The system mean time to first failure was also studied.
Keywords: İstatistik ve Olasılık